ANALISIS POLA AKSES INTERNET DENGAN INTERVENSI EDUKASI DAN FILTERING BERDASARKAN LOG PROXY SQUID SERVER - , Mauladi, Widyawan, S.T, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Currently the Indonesian government tried to improve Information Technology resources. Implementation can be seen from the procurement of infrastructure, applications and Internet access. But efforts to measure and improve utilization of these things are still minimal. This research attempts to analyze the patterns of Internet access by intervention in the form of virtual education using educational video and proxy filtering, then look at the pattern of access changes that occur through the Squid proxy log analysis. The results showed an increase in access to positive and negative content decreased access. The results of this research seeks to provide strategic advice on the use of Internet access, particularly to local government to use the Internet can be more optimal.